Pemantauan Dinamika Land Surface Temperature dan Indeks Spektral (NDVI) Menggunakan Landsat ETM+ dan OLI/TIRS di Lanskap Jember Selatan: Monitoring Land Surface Temperature and Spectral Indices (NDVI) Dynamics Using Landsat ETM+ and OLI/TIRS in the Southern Jember Landscape - Sholihah, Rizqi I'anatus; Putra, Rizki Auliansyah; Santosa, Lenalda Febriany; Atmadja, Krisologus Genesa Ruby; Wulandari, Verlina Intan; Rahman, Basuki; Islami, Muflihatul Maghfiroh; Kusneti, Monica (JURNAL HUTAN TROPIKA, 2025)
Landscape transformation driven by rapid urbanization is a primary determinant of microclimate change in peri-urban regions. This study aims to analyze the spatiotemporal dynamics of land surface temperature (LST) and its relationship with vegetation density (Normalized Difference Vegetation Index/NDVI) in the Southern Jember landscape. Utilizing Landsat 7 ETM+ and Landsat 8 OLI/TIRS imagery from 2001, 2013, and 2025, this research evaluates the impact of land cover changes on the regional thermal regime and vegetation index variability. The results reveal a fundamental landscape transition, where the dominance of paddy fields shrank drastically from 66.400 ha (2001) to 13.800 ha (2025), replaced by a massive expansion of settlements reaching 82,900 ha. This shift triggered a significant surface urban heat island (SUHI) phenomenon. Settlement areas recorded an extreme maximum LST of 38,1°C in 2025, a sharp increase compared to the initial study period. Spectral analysis confirms that the rise in LST has a negative correlation with NDVI. This evidence suggests that the loss of vegetation biomass and the increase in impervious surfaces due to uncontrolled urbanization are the primary drivers of environmental warming in South Jember. These findings underscore the urgency of climate-mitigation-based spatial planning strategies for regional sustainability.